Characteristics of Microplastic in Selected Marine Sponges from Pasir Putih Situbondo, East Java, Indonesia - Fauziah, Natasya Febriani; Muzaki, Farid Kamal; Fajrinia, Naurah Rizki; Aunurohim, Aunurohim; Saptarini, Dian (HAYATI Journal of Biosciences, 2025)
Microplastics (MPs) are global concern due to their presence in various ecosystems and their tendency to have a negative impact on organisms. MPs are plastic fragments with a small size ranging from >1 μm to <5 mm, which are easily ingested by marine organisms, including marine sponges. As filter-feeding organisms, sponges can accumulate MPs in their bodies. This study aims to analyze the physical and chemical characteristics and the abundance of MPs in seawater and sponges. Three species of marine sponges (Xestospongia testudinaria/XT, Aaptos suberitoides/AS, and Clathria sp./CR) with ten replicate samples were collected from Batu Lawang reef in Pasir Putih, Situbondo, East Java, Indonesia. MPs samples were also collected from the water column (surface and sea bottom at a depth of ±6-7 m). Analysis of physical characteristics (shape, color, and size) performed using a stereo microscope and Optilab, whilst chemical characteristics (type of polymer) was analyzed using ATR-FTIR. A one-way ANOVA test followed by Tukey's HSD (both at p = 0.05) were performed to determine the difference in MPs density from each species. There was no significant difference in term of density in XT and AS, with average density of 60.6 and 66.9 particles/g wet weight (ww), respectively. The density in CR was significantly higher, with the value of 86.7 particles/g (ww). In the water column, the density was 20-27 particles/L (surface sample) and 37-84 particles/L (sea bottom). All particles dominated by black fragments with sizes ranging from 0 to 60 μm, and the polymer type is polypropylene (PP).